System Design for Cost Maquicentro Footwear School of Industrial Engineering. UNMSM. - Quispe Atúncar, Carlos (2001)
The paper presents a methodology for the design of a "system cost for Maquicentro shoe-San Marcos School of Industrial Engineering," taking into account the volume and diversity of production (business size), the control needs the costs of installation, implementation and maintenance. Indirect costs allocable to each work order are defined by selecting the appropriate bbase as distribution.